Clinical medicine. (Libertas Academica, 2008)
Clinical Medicine: Blood Disorders is an international, open access, peer reviewed journal which considers manuscripts on all aspects of the diagnosis, management and prevention of blood disorders, in addition to related genetic, pathophysiological and epidemiological topics.